(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
A cotton skin and a waterproof but permeable Gore-Tex skin were designed for the thermal manikin &#8220Tore&#8221 to simulate different sweating styles (the wet cotton skin inside and Gore-Tex skin outside to simulate the sweating style of thermal manikin &#8220Walter&#8221, and Gore-Tex skin inside with wet cotton skin outside to simulate the sweating style of thermal manikins &#8220Newton&#8221). The evaporative resistances of two skin combinations with clothing ensembles were compared at different environmental conditions. In addition, the total evaporative resistance of clothing ensemble was calculated by both the heat loss method (option 1) and the mass loss method (option 2) according to ASTM F 2370. We found that the effect of different sweating mechanisms on the clothing evaporative resistance should be considered. The results showed that the total evaporative resistances calculated by option 2 were more accurate than values in option 1 under the isothermal condition. It was also found that differences of the total evaporative resistance between two skin combinations with clothing ensembles decreased with the increasing clothing ensemble layer. In a non-isothermal condition, the total evaporative resistance calculated by option 1 was more accurate than the value obtained in option 2, which was due to the lower ambient temperature and condensations between each adjacent layer.